The Economic Surplus in Argentina: The Neoliberal Stage (1991-2001) Versus Neo-Developmental Stage (2002-2015) (2018)
This work proposes to study the evolution of the Argentine political economy comparing the periods of convertibility (1991-2001) and postconvertibility (2002-2015), recovering the analysis offered by the economic surplus theory (in its structuralist and Marxist versions) and offering instruments to measure it. The interest in these stages arises from the existing controversies regarding the continuities and ruptures between the neoliberal order and the neo-developmental model that was deployed during Kirchner's governments. The analysis not only focuses in the evolution of the social wealth and its distribution between both projects, but also tries to combine it with the concept of accumulation regime.